Understanding the role of perceived ownership in access-based services: Insights from an analysis of mobility service offerings - Roßmann, Bernhard; Hartmann, Evi; Moser, Roger (VHB Tagung 2017, 2017)
The phenomena of access-based services and related concepts underline the recent rise of the Service Dominant logic in the management literature. However, the resulting variety of access-based models increasingly fragments property rights in practice and therefore blurs the line between ownership and access. This paper aims to address these fuzzy lines in the context of access-based services. For this purpose, subjective feelings of ownership that are based on psychological ownership theory are conceptualised as the missing link between those lines. While a perception of ownership may result in an increase of value attribution from users, burdens of ownership may also be imposed. To explore the role of perceived ownership in access-based services, a taxonomy that integrates both traditional as well as recently established access-based services is developed. As the determinants of perceived ownership are highly contextual, the taxonomy development is carried out within the context of mobility services. Such services involve high levels of value attributions based on psychological perceptions and emotions and might be comparable to other access-based services. In our analysis, features that alter a consumer’s experience during access compared to ownership are interpreted as the determinants of perceived ownership and identified by a review of the access-based mobility service literature. An analysis and comparison of access-based services highlights the enabling effects of technology advances and shifting effects of new preferences in consumer behaviour. To conclude, resulting effects on perceived value attributions within access-based services and suggestions on the role of perceived ownership in future research on access-based services are discusse